Sie sind auf Seite 1von 3

CUBING OF A BINOMIAL Cube Sum A cubed binomial (sum) is equal to the cube of the first, plus three times

the s quare of the first by the second, plus three times the first by the square of th e second, plus the cube of the second. (a + b)3 = a3 + 3 a2 b + 3 a b2 + b3 (x + 3)3 = x 3 + 3 x2 3 + 3 x 32 + 33 = = x 3 + 9x2 + 27x + 27 Cube Difference A cubed binomial (difference) is equal to the cube of the first, minus three tim es the square of the first by the second, plus three times the first by the squa re of the second, minus the cube of the second. (a - b)3 = a3 - 3 a2 b + 3 a b2 - b3 (2x - 3)3 = (2x)3 - 3 (2x)2 3 + 3 2x 32 - 33 = = 8x 3 - 36 x2 + 54 x - 27 Examples 1(x + 2)3 = x3 + 3 x2 2 + 3 x 22 + 23 = = x3 + 6x2 + 12x + 8 2(3x - 2)3 = (3x)3 - 3 (3x)2 2 + 3 3x 22 - 23 = = 27x 3 - 54x2 + 36x - 8 3(2x + 5)3 = (2x)3 + 3 (2x)2 5 + 3 2x 52 + 53 = = 8x3 + 60 x2 + 150 x + 125 1. Monomial by Polynomial Example a.) b(ab+b+1+x) = ab+b+b+bx ->distribute b to each of the terms in the pare ntheses. b.) 3x(y+y+2z-zyx) = 3xy+3xy+6xz-3xzy

2. Square of Binomials Steps: (shortcut) Example a.) (x+y) = (x) + (x)(y)(2) + (y) = x+2xy+y First, square the first term (x). Second, multiply the first term (x) , the last term (y) and the exponent (2), since it is in the second power. Last, square th e last term (y). By following the steps, it gives us x +2xy+y as our final answer.

b.) (2x+5y) = (2x) + (2x)(5y)(2) + (5y) = 4x+20xy+25y c.) (a-4) = (a) + (a)(-4)(2) + (-4) = a^4-8a +16 NOTE: This rule is only applicable on the square of binomials. In some of the ex amples, we can use a^ to show an exponent, s0 2^2 means (2) = 4.

3. Sum and Difference of Binomials Steps: (shortcut) Example a.) (b+c)(b-c) = (b) - (c) = b - c If the given terms (values) are the same but they have opposite signs in between , we are to square the first term (b) and the second term (c). Then we will use the negative sign in between. Using the FOIL method, we would have to delete -bc and bc (in the process) because the answer is 0. Therefore, the final answer is b -c . b.) (3m -4)(3m +4) = (3m) - (4) = 9m^4 - 16 c.) (4x-7y)(4x+7y) = (4x) - (7y) = 16x - 49y

4. Binomials of the form (ax+b)(cx+d) where a, b, c & d are constants. Steps: (shortcut) Example a.) (2x+1)(x-3) = 2x^4 + (-6x ) + x + (-3) = 2x^4 - 5x - 3 We can come up with the answers mentally by using the FOIL method. First, we wil l get the product of the first terms, 2x & x. The product is 2x^4. Second, we will get the sum of the outer terms, 2x & -3 = -6x, and the inner terms 1 & x = x. To ge t the sum, x-6x = -5x. Lastly, we will get the product of the last terms 1 & -3, th e produuct is -3. Therefor the final answer is 2x^4 - 5x - 3. b.) (3x-5)(4x+3) = 12x + 9x + (-20x) + (-15) = 12x -11x -15 c.) (5x-7)(8x-1) = 40x + (-5x) + (-56x) + 7 = 40x -61x + 7 5.) Sum and Difference of Cubes Steps: (shortcut) Example a.) (2x-1)(4x+2x+1) = (2x) + (-1) = 8x - 1 First, we should see to it that the terms in the second parentheses coincides wi th the first. To check, the first term in the second parentheses, 4x, should be t he product if we square the first term in the first parentheses, 2x. That is, (2 x) = 4x. If the answer is correct, we should proceed now to step two. Second, check if the second term in the second parentheses, 2x, is the product o f the terms in the first parentheses, 2x & -1; only that the sign should be oppo

site. That is, (2x)(-1) = -2x -> 2x. If the answer is correct, we should proceed to step three. Third, check if the last term in the second parentheses, 1, is the square of the first term in the first parentheses, -1. That is, (-1) = 1. If the second parent heses coincides with the first by following the steps given previously, we can n ow proceed to the last step. Lastly,we can now give the final answer by finding the cube root of the first pa rentheses (2x-1). (2x) = 8x ; (-1) = -1. Therefore, the final answer is 8x - 1 NOTE: We can follow the first to the third step mentally. b.) (y+2)(y-2y+4) = (y) + (2) = y + 8 c.) (x -2y)(x^4+2xy+4y) = (x) + (-2y) = x^6 - -8y^3 6.) The Square of a Trinomial Steps: (shortcut) Example a.) (x+2y-3z) = (x) + (2y)+ (-3z) + (x)(2y)(2) + (x)(-3z)(2) + (2y)(-3z)(2) = x + 4y + 9z + 4xy - 6xz - 12yz First, we should square the first term, x, the second term, 2y, and the third te rm, 3z. Written as, (x) = x ; (2y) = 4y ; (-3z) = 9z . Second, we should get the product of the first term, x, and the second term, 2y, and the exponent 2. Written as, (x)(2y)(2) = 4xy. Third, we should get the product of the first term, x, the third term, -3z, and the exponent 2. Written as, (x)(-3z)(2) = -6xz Lastly, we should get the product of the second term, 2y, the third term, -3z, a nd the exponent 2. Written as, (2y)(-3z)(2) = -12yz Combining all the answers, we now have x + 4y + 9z + 4xy - 6xz - 12yz . b.) (-3x+y-5z) = (-3x) + (y) + (-5z) + (-3x)(y)(2) + (-3x)(-5z)(2) + (y)(-5z)(2) = 9 x + y + 25z -6xy + 30xz - 10yz c.) (-x-2xy-5y) = (-x) + (-2xy) + (-5y) + (-x)(-2xy)(2) + (-x)(-5y)(2) + (-2xy)(-5y) (2) = x + 4xy + 25y + 4xy + 10xy + 20xy Exercises: